Indonesia Literatur Review: Akuntansi Sektor Publik dalam Mewujudkan Transparansi dan Akuntabilitas Keuangan Negara - Cintya Dwi Putri Supriyatna; Mealvin Febriani Sulistia; Yuniati (JAPP: JURNAL AKUNTANSI, PERPAJAKAN DAN PORTOFOLIO, 2026)
The management of state finances demands high standards of transparency and accountability to achieve good governance. This study aims to conduct a literature review on the role of public sector accounting in strengthening the transparency and accountability of state finances. Through an analysis of 20 journal articles, it was found that the application of public sector accounting systems, including the implementation of accrual-based accounting and the Central Government Accounting System (SAPP), contributes significantly to improving the quality of financial reports and the performance of government agencies. Public sector accounting serves as a strategic tool to provide open fiscal information and minimize opportunistic behavior as well as the risk of fraud. Furthermore, the integration of digital technology and the strengthening of internal controls are crucial factors in facing the challenges of accounting evolution in the modern era. The results of this review confirm that transparency and accountability are the main pillars in state financial management that cannot be separated to achieve public welfare.